Odpowiedzi

Najlepsza Odpowiedź!
2009-09-19T22:07:39+02:00
30/√3-√5+√2=30(√3-√5-√2)/(√3-√5-√2)(√3-√5+√2)=
30(√3-√5-√2)/(√3-√5)²-2)=30(√3-√5-√2)/(3-2√15+5-2)=30(√3-√5-√2)/(6-2√15)=
30(√3-√5-√2)(6+2√15)/(6-2√15)(6+2√15)=
30(√3-√5-√2)(6+2√15)/(36-60)=30(√3-√5-√2)(6+2√15)/(-24)=
5(-√3+√5+√2)(6+2√15)/(4)
3/∛9-∛6+∛5=
3( (∛9-∛6)²-∛9-∛6)∛5+∛25)/(∛9-∛6+∛5)[(∛9-∛6)²-(∛9-∛6)∛5+∛25)]=
3( (∛9-∛6)²-∛9-∛6)∛5+∛25)/(∛9-∛6)³-5

2009-09-19T22:54:11+02:00
30/√3-√5+√2=(30-√15+√6)/√3=(30√3-3√5+3√2)/3=10√3-√5+√2

3/∛9-∛6+∛5=(3-∛54+∛45)/∛9=(3∛3-3∛6+3∛5)/3=∛3-∛6+∛5